The relationship between clinical education and nursing students' patient safety competencies - Dyah Wiji Puspita Sari; Yuni Sufyanti Arief; Ahsan Ahsan (PAGEPress Publications, 2024)
Students play a crucial role in contributing to patient safety issues, a contribution that is significantly influenced by the implementation of clinical education. This study aimed to investigate the impact of clinical education on the achievement of patient safety goal competencies among nursing students. A cross-sectional study was conducted among 125 students in a nursing professional program at Sultan Agung Hospital in Semarang, Central Java, Indonesia. A total sampling technique was employed for sample recruitment. Data for the dependent variable were collected using an observation sheet, while data for the independent variable were collected using a structured questionnaire. Bivariate data analysis was performed using the Chi-square test. The bivariate analysis revealed a significant relationship between the implementation of clinical education and the achievement of patient safety goal competencies, with a p-value of 0.000 (p < 0.05) and a correlation coefficient of 0.609. The achievement of patient safety goal competencies can be facilitated through the implementation of optimal clinical education. Therefore, the implementation of clinical education must include a clinical education model based on the community of practice, making it easier for students to implement patient safety goals.